Renin–angiotensin–aldosterone system activation in plasma as marker for prognosis in critically ill patients with COVID-19: a prospective exploratory study - Katharina Krenn; Felix Kraft; Luana Mandroiu; Verena Tretter; Roman Reindl-Schwaighofer; Theresa Clement; Oliver Domenig; Matthias G. Vossen; Gregor Riemann; Marko Poglitsch; Roman Ullrich (Annals of Intensive Care)
Abstract Background Acute respiratory distress syndrome (ARDS) associated with coronavirus infectious disease (COVID)-19 has been a challenge in intensive care medicine for the past three years. Dysregulation of the renin–angiotensin system (RAS) is linked to COVID-19, but also to non-COVID-19 ARDS. It is still unclear whether changes in the RAS are associated with prognosis of severe COVID-19. Methods In this prospective exploratory study, blood samples of 94 patients with COVID-19 were taken within 48 h of admission to a medical ward or an ICU. In ICU patients, another blood sample was taken seven days later. Angiotensin (Ang) I-IV, Ang 1–7, Ang 1–5 and aldosterone concentrations were measured with liquid chromatography tandem mass spectrometry (LC–MS/MS) followed by calculation of markers for activities of renin (PRA-S) and ACE (ACE-S), alternative RAS activation (ALT-S) as well as the ratio of aldosterone to Ang II (AA2R). Angiotensin-converting enzyme (ACE) and ACE2 concentrations were measured by LC–MS/MS-based assays. All RAS parameters were evaluated as predictors of 28-day and 60-day survival using receiver operating characteristic and multivariate logistic regression analysis. Results AA2R at inclusion was a predictor of 60-day survival for ICU patients with an AUROC of 0.73. Ang II and active ACE2 were inversely associated with survival (OR 0.07; 95%CI 0.01, 0.39 and OR 0.10; 95%CI 0.01, 0.63) while higher Ang 1–7 predicted favorable outcome (OR 6.8; 95%CI 1.5, 39.9). ICU patients showed higher concentrations of all measured angiotensin metabolites, PRA-S, ALT-S and active ACE2, and lower ACE-S and AA2R than patients in the medical ward at inclusion. After seven days in the ICU, Ang I, Ang II, Ang III and Ang IV concentrations decreased, while ACE and ACE2 levels increased. Ang I, PRA-S, Ang 1–7 and Ang 1–5 concentrations correlated with the SOFA score both at the time of inclusion and after seven days, and driving pressure after seven days. Conclusions AA2R at inclusion predicted 60-day survival with moderate sensitivity, revealing a dissociation between unchanged aldosterone and increased Ang II levels in the most severely ill COVID-19 patients. After adjustment for confounders, Ang 1–7 as the final metabolite of alternative RAS was predictive for survival.